Tooth agenesis in osteogenesis imperfecta related to mutations in the collagen type I genes. (13th September 2016) - Malmgren, B; Andersson, K; Lindahl, K; Kindmark, A; Grigelioniene, G; Zachariadis, V; Dahllöf, G; Åström, E
Abstract : Background: Osteogenesis imperfecta (OI) is a heterogeneous group of disorders of connective tissue, mainly caused by mutations in the collagen type I genes ( COL1A1 and COL1A2) . Tooth agenesis is a common feature of OI. We investigated the association between tooth agenesis and collagen type I mutations in individuals with OI. Subjects and methods: In this cohort study, 128 unrelated individuals with OI were included. Panoramic radiographs were analyzed regarding dentinogenesis imperfecta (DGI) and congenitally missing teeth. The collagen I genes were sequenced in all individuals, and in 25, multiplex ligation‐dependent probe amplification was performed. Results: Mutations in the COL1A1 and COL1A2 genes were found in 104 of 128 individuals. Tooth agenesis was diagnosed in 17% (hypodontia 11%, oligodontia 6%) and was more frequent in those with DGI ( P = 0.016), and in those with OI type III, 47%, compared to those with OI types I, 12% ( P = 0.003), and IV, 13% ( P = 0.017). Seventy‐five percent of the individuals with oligodontia (≥6 missing teeth) had qualitative mutations, but there was no association with OI type, gender, or presence of DGI. Conclusion: The prevalence of tooth agenesis is high (17%) in individuals with OI, and OI caused by a qualitative collagen I mutation is associated with oligodontia.